Spatial variation analysis of the number of growing days for fruit trees in Iraq - Mutar, Zeyad; Hamad, Natheer (Al-Adab Journal, 2025)
Objective: The research aims to determine the beginning, end, and duration of the growing season for fruit trees in Iraq using statistical methods. Subsequently, spatial and temporal variance analysis will be conducted on the duration of the growing season according to the different regions of Iraq. This will help identify the most suitable areas for fruit tree cultivation based on the growing season. Methods: The researcher utilized quantitative and statistical methods to determine the growing season and its duration. The most effective method identified in this field was the use of a third-degree polynomial function to achieve the desired results of this study after establishing the lower and upper thresholds for growth for each crop among the fruit crops under investigation. Climatic data was collected for daily minimum and maximum temperatures from seven meteorological stations distributed across Iraq’s regions for a 42-year period from 1980 to 2022. Results: The research results revealed a clear spatial variation in the number of days of the growing season for palm trees. Sulaymaniyah in northeastern Iraq exhibited the highest total number of days per year at 204 days, while Mosul had the lowest number of days at 149 days per year. Regarding citrus fruits, the wettest station in western Iraq had the highest total number of days for the growing season at 182 days per year, with the lowest number of days observed in the southern region of Iraq at 105 days per year. While the total number of days for the grapevine growth season was the highest in Sulaymaniyah at 158 days per year, the lowest total number of days was recorded in Mosul at 112 days per year. As for pomegranate trees, Sulaymaniyah also had the highest total number of days for the growth season at 159 days per year, while the lowest was observed in both Mosul and Baghdad at 103 days per year for each. Conclusion: Daily minimum and maximum temperatures are among the most crucial climatic elements in determining the growing season and its duration. By examining the variation in daily temperatures across different regions of Iraq, a clear disparity in the number of days of the growing season has been revealed. Through this variation, we can identify the areas that are suitable and most suitable for cultivating fruit trees based on the growing season.